2022
DOI: 10.33448/rsd-v11i11.33072
|View full text |Cite
|
Sign up to set email alerts
|

Cuidados de enfermagem a pacientes acometidos com infarto agudo do miocárdio

Abstract: Dentre as diversas doenças cardiovasculares, destaca-se o Infarto Agudo do Miocárdio que é uma lesão que acomete o músculo cardíaco, ocasionada pela diminuição inadequada da oferta de nutrientes e oxigênio, induzindo a obstrução do fluxo sanguíneo, podendo desenvolver necrose tecidual. O enfermeiro é o profissional qualificado para realização de diversas ações e cuidados assistenciais ao paciente com IAM. Logo, a pesquisa visa descrever os fatores associados e os cuidados de enfermagem ao paciente acometido co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
0
4
0
5
Order By: Relevance
“…In addition to that, Santos and colleagues [7] highlighted in their study that the main risk factors associated with the development of AMI are smoking, family history of cardiovascular diseases (CVDs), serum level of Low-Density Lipoproteins (LDL), Systemic Arterial Hypertension (SAH), and Diabetes Mellitus. Therefore, family history is also a factor of great relevance, as when a "relative" has already presented the pathology, the individual is more likely to develop the disease due to hereditary factors, aggravating the factors that favor the development of AMI [8].…”
Section: Factors Associated With Acute Myocardial Infarctionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to that, Santos and colleagues [7] highlighted in their study that the main risk factors associated with the development of AMI are smoking, family history of cardiovascular diseases (CVDs), serum level of Low-Density Lipoproteins (LDL), Systemic Arterial Hypertension (SAH), and Diabetes Mellitus. Therefore, family history is also a factor of great relevance, as when a "relative" has already presented the pathology, the individual is more likely to develop the disease due to hereditary factors, aggravating the factors that favor the development of AMI [8].…”
Section: Factors Associated With Acute Myocardial Infarctionmentioning
confidence: 99%
“…Ponte and Silva [9] reported in their study that precordial pain was reported by all patients, being present since admission. The authors also reported on the main signs and symptoms, with emphasis on headache, difficulty in sleeping, nausea, cold skin, hypertension, bradycardia, anxiety, and pain [8]. It was found that, according to the third chronic guideline for heart failure, the etiology of heart failure is associated with dilated and ischemic cardiomyopathy, uncontrolled systemic arterial hypertension, and Diabetes Mellitus, as well as hospitalizations for the decompensation of this condition [10].…”
Section: Factors Associated With Acute Myocardial Infarctionmentioning
confidence: 99%
See 2 more Smart Citations
“…ORCID: 0000-0003-4579-3588 Maycon Richard Gomes da Silva 1 ORCID: 0000-0001-7985-8154 Meyreane de Lima Borges 2 ORCID: 0000-0003-2113-5628 Sthéfany Martins Souza de Oliveira 3 ORCID: 0000-0003-0875-132X Milena Maria Picolin 1 ORCID: 0000-0002-3371-7396 Francieli Tozatti Ficagna 4 ORCID: 0000-0003-2902-5992 1 Faculdades Associadas de Santa Catarina. Santa Catarina, Brasil.…”
Section: Cladis Loren Kiefer Moraes 1*unclassified